Distribuição intragástrica de refeição e esvaziamento gástrico na dispepsia funcional: uma análise multissegmentar - Ietsugu, Marjorie do Val [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Gastrointestinal motility abnormalities are involved in the etiology of functional dyspepsia (FD), which is characterized by several manifestations with no organic disease that explain the symptoms; it fits into the functional gastrointestinal disorders. Scintigraphy is the gold standard technique to FD assessment; however there is no standard application for evaluate gastric motility alterations. The aim of this study was to evaluate, by scintigraphy, gastric total emptying (GE), regional and intragastric distribution of meal (IDM) using two segmentations and to assess frequency and amplitude of contractions in proposed segmentations in dyspepsia by dynamic scintigraphic. Thirty four individuals, 20 normal and 14 dyspeptics were evaluated, selected according to Rome III. The test meal and protocols of static images acquisition obtained immediately and at intervals of 60, 120 and 240 minutes after ingestion of the test meal were recommended by consensus; in addition, dynamic images of 1 Hz were acquired after immediate image and before image referent to 60 minutes of ingestion. Data were analyzed in MatLab® with images segmentation in proximal and distal regions. Total GE in dyspepsia was similar to normal individuals. However, the regional GE and the IMD were altered in dyspepsia, independently of segmentation, indicating GE should be evaluated not only by the test meal retention, but also considering classical parameters and visual image analysis. Dynamic acquisition in associated with statics images represented a tool to measure regional GE, allowing quantification of the IMD and dominant frequencies (DF) and amplitudes of regional gastric contractions. Differences between groups were observed independently of segmentation, encouraging the use of segmentation according to half of gastric area due to minor proximal regional influence. Although DF hasn't differed in both regions between groups, smaller amplitude of contraction ...

Alterações da motilidade gastrintestinal estão envolvidas na etiologia da dispepsia funcional (DF) que apresenta sintomatologia vasta sem qualquer causa orgânica que a justifique, enquadrando-se no grupo de doenças funcionais do trato gastrintestinal. A cintilografia é técnica padrão-ouro para a avaliação da DF, todavia não há uma padronização para sua utilização na avaliação motora gástrica. O objetivo deste trabalho foi avaliar, na cintilografia, o esvaziamento gástrico (EG) total, regional e a distribuição intragástrica de refeição (DIR) empregando duas segmentações e analisar a frequência e amplitude das contrações nas segmentações propostas na dispepsia por meio dos sinais cintilográficos dinâmicos. Foram avaliados 34 indivíduos, 20 normais e 14 dispépticos, selecionados de acordo com Roma III. A refeição-teste e o protocolo de aquisição das imagens estáticas adquiridas imediatamente e em intervalos de 60, 120 e 240 minutos após a ingestão da refeição-teste foram preconizados pelo consenso de 2008; ademais, imagens dinâmicas de 1 Hz foram adquiridas após a imagem imediata e antes daquela referente a 60 minutos da ingestão. Os dados foram analisados em MatLab® com segmentação das imagens em regiões proximal e distal. O EG total em dispépticos foi semelhante àquele de indivíduos normais. Todavia, o EG regional e a DIR mostraram-se alterados na dispepsia, independente da segmentação, sinalizando que o EG não deve ser avaliado unicamente por meio de quantificações de retenção da refeição-teste, devendo-se também considerar parâmetros clássicos de avaliação e a análise visual das imagens. A aquisição dinâmica associada às estáticas mostrou-se como uma ferramenta de avaliação do EG regional, permitindo quantificações da DIR e das frequências dominantes (FD) e amplitudes das contrações regionais. Diferenças entre os grupos foram observadas independente da...
Intragastric distribuition of meal and gastric emptying in functional dyspepsia: a multi-segmental analysis
Keywords: Exploração por radioisotopos; Gastroenterologia; Dispepsia; Sistema gastrointestinal - Motilidade; Gastroenterology